Mathematical software : (World Scientific, 2002)
Proceedings of the First Intl Congress of Mathematical Software, held August 17-19, 2002 in Beijing, China. Aimed at software developers in mathematics and programming mathematicians, but also provides opportunities to discuss the topics with mathematicians.